Dynamics of linalool and its derivatives enantiomers in Camellia sinensis var. Assamica “Hainan dayezhong” - Ying Zhou; Junjie Tian; Hainuo Hong; Yang Gao; Yunchuan He; Zeng-Rong Zhu (Food Chemistry: X)
We here analyzed changes in the proportion and content of chiral isomers of linalool and its derivatives in “Hainan dayezhong” throughout its life cycle from tea tree growth and tea manufacturing to brewing. The chiral isomers of aromatic compounds present in fresh tea leaves were found to undergo substantial diurnal and seasonal changes during tea tree growth, and their proportions varied slightly across different leaf positions. The chiral isomer content of linalool and its derivatives was consistently higher in stems than in leaves. Pest and disease stress significantly increased the proportion and content of type-R aroma. The proportion of chiral isomers underwent no considerable change during black tea manufacturing. However, their content varied dramatically among different processes. Diversity in the proportion and content of chiral isomers was observed in the wild tea tree. Further research should focus on breeding “Hainan dayezhong” wild resources to generate clones with high aroma quality.